(untitled) (SCIÉNDO INGENIUM, 2024)
The objective of this study is to evaluate the gold resource potential in the Alto Chicama Basin (CAC) using a multi-criteria methodology based on Geographic Information Systems (GIS). Key criteria such as geological units, metallic mining concessions, geological faults, metallic mineral deposits, geochemical data, and remote sensing analyses were selected, weighted, and modeled in a GIS environment to generate a comprehensive zoning map of gold potential. The results of the multi-criteria analysis reveal that the northern and southeastern areas of the basin exhibit high gold potential, suggesting that these areas are particularly favorable for future mining exploration. These zones stand out due to their correlation with critical geological and geochemical characteristics, validating the effectiveness of the proposed model. In conclusion, the combination of GIS and multi-criteria methodologies has proven to be a robust and effective tool for strategic planning in mining exploration.